Misconceptions Over Gender Inequalities in Islamic Law and Pakistan: A Comparative Analysis - Dr. Sohaib Mukhtar; Deeba, Malieka Farah; Ahmad Talha (AL-IDRAK JOURNAL, 2023)
Misconceptions related to inequalities between male and female persons in Pakistan are existed in the mind of people around the World. People think that theses existing inequalities are linked with Islamic Law and its strict principles laid down in verses of Holy Quran and traditions of Holy Prophet Muhammad ﷺ. The fact is that inequalities exist in Pakistani society between male and female not because of strict principles of Islamic Law but because of feudal mindset and because of low literacy rate and lack of knowledge. Islamic Law does not create inequalities between male and female persons as it is misunderstood by the majority and also is badly portrayed by the people who portray themselves as true followers of Islamic Law which actually is incorrect. Apart from feudal mindset and low literacy rate, the Government of Pakistan is duty bound under 34 of the Constitution of Pakistan 1973 to create good atmosphere for all and ensure full participation of women in all spheres of life but it is unsuccessful to create a friendly atmosphere for women. Low literacy rate in Pakistan is not because of religion as Prophet Muhammad ﷺ stated that seeking knowledge and education is compulsory for every believer (whether man or woman). It is also emphasized under Constitution of Pakistan 1973 thus it is quite unfair to blame the State of Pakistan and Islamic Law for gender inequalities in Pakistan as both the verses of Holy Quran, traditions of Holy Prophet Muhammad ﷺ and the Constitution of Pakistan 1973 emphasize on equality before law without discrimination, therefore negative propaganda against Islamic Law and the State of Pakistan should be stopped and the World is required to help the Government of Pakistan to eliminate inequalities and to promote education throughout Pakistan without discrimination as to gender, race, religion, place of birth.